Ormeloxifene in the management of abnormal uterine bleeding in tertiary care centre South Kerala - Chandran, Rinu S.; Adaline Thangam, T. F.; Joy, Dhiya P.; Rose, Adline (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: AUB is the most common presentation in the reproductive age group. Many females suffer from AUB and its related effects. A study on the effectiveness of an easily available drug (ormeloxifene) with an easy dosing schedule was done and its wonderful role in controlling the symptoms and improvement of quality of life of a female with no financial burdens and surgical morbidity was studied. Methods: A hospital based prospective observational study was conducted among women attending the outpatient clinic of OBG department at Dr Somervell Memorial CSI Medical College, Karakonam, Trivandrum district. Results: Total 50 women with AUB took part in the study. 62% had menstrual duration of <7 days with regular cycles (84%). 86% of them had history of passage of clots. 48% of them had dysmenorrhea. Efficacy of ormeloxifene was assessed by using PBAC score and haemoglobin level measurement. A repeated measures ANOVA with a Greenhouse-Geisser correction determined mean PBAC score differed significantly between months. Post hoc analysis with a Bonferroni adjustment revealed PBAC score was statistically significantly decreased from pre-intervention to 3 months to 6 months. There is statistically significant difference with respect to haemoglobin level improvement. Conclusions: Ormeloxifene is an excellent drug in controlling AUB as evidenced by the PBAC score and haemoglobin levels. Ormeloxifene has better compliance and acceptability. It is cost effective with a simple dosage schedule. A significant decrease in the menstrual blood loss and marked improvement in the hemoglobin concentration.